2020
DOI: 10.1002/cjce.23751
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of dry pressure drop and flow behaviour of gas flow through sieve plate packing

Abstract: Sieve plate packing is a newly developed packing that has been used in several industries due to its simple structure and operating flexibility, and no liquid flooding. In this work, first, systematic experiments were conducted to measure the pressure drop of gas flow through six sieve plate packings. The results indicated that the geometric characteristics of the packing have complicated effects on the pressure drops. Based on this, CFD simulations on the gas flow field were conducted using the realizable k‐ε… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Results show that the interfacial area and liquid holdup decreased with increase in the contact angle. Qiao et al [134] conducted systematic experiments to measure the pressure drop of a gas flow through six sieve plate packings. The results indicated that the geometric characteristics of the packing had complicated effects on the pressure drop.…”
Section: Hydrodynamics Heat and Mass Transfer 41 Pressure Drop And Li...mentioning
confidence: 99%
“…Results show that the interfacial area and liquid holdup decreased with increase in the contact angle. Qiao et al [134] conducted systematic experiments to measure the pressure drop of a gas flow through six sieve plate packings. The results indicated that the geometric characteristics of the packing had complicated effects on the pressure drop.…”
Section: Hydrodynamics Heat and Mass Transfer 41 Pressure Drop And Li...mentioning
confidence: 99%